Sex-related Changes in Circadian Rhythm of Inflammatory and Oxidative Stress Markers in CKD (Iranian Journal of Kidney Diseases, 2021)
Introduction. Circadian system is deeply involved in renal function. The circadian timing system may be disrupted in chronic kidney disease (CKD) patients. Gender differences in CKD have been reported. This research aimed to investigate the gender differences in the circadian rhythm of inflammatory and oxidant markers of CKD. Methods. Male, intact female, and ovariectomized (OVX) female rats (twenty-four in each group) were randomly assigned to control and CKD groups. The rats were further divided into day (12:00 p.m.) and night (12:00 a.m.) subgroups. Evaluations of each sample were carried out a day after the last day of adenine administration. Results. Final results revealed that the circadian rhythm of plasma melatonin , kidney malondialdehyde (MDA), and transforming growth factor- β (TGF-β) levels in CKD group were the same as the control group. Melatonin and total antioxidant capacity (TAC) levels significantly decreased in the CKD group compared with the control group in day and night subgroups, whereas MDA and TGF-β levels increased. Male group in comparison with the intact female group significantly showed less melatonin and TAC but higher MDA and TGF-β levels which could be due to CKD. Conclusion. Findings of this study represent gender differences in circadian rhythm amplitude of inflammation, melatonin, and oxidative stress in CKD animals, probably in favor of female sex steroids. These findings emphasize on the importance of gender differences in CKD progression; therefore, considerable attention must be paid to gender in the treatment of CKD.Introduction. Circadian system is deeply involved in renal function. The circadian timing system may be disrupted in chronic kidney disease (CKD) patients. Gender differences in CKD have been reported. This research aimed to investigate the gender differences in the circadian rhythm of inflammatory and oxidant markers of CKD. Methods. Male, intact female, and ovariectomized (OVX) female rats (twenty-four in each group) were randomly assigned to control and CKD groups. The rats were further divided into day (12:00 p.m.) and night (12:00 a.m.) subgroups. Evaluations of each sample were carried out a day after the last day of adenine administration. Results. Final results revealed that the circadian rhythm of plasma melatonin , kidney malondialdehyde (MDA), and transforming growth factor- β (TGF-β) levels in CKD group were the same as the control group. Melatonin and total antioxidant capacity (TAC) levels significantly decreased in the CKD group compared with the control group in day and night subgroups, whereas MDA and TGF-β levels increased. Male group in comparison with the intact female group significantly showed less melatonin and TAC but higher MDA and TGF-β levels which could be due to CKD. Conclusion. Findings of this study represent gender differences in circadian rhythm amplitude of inflammation, melatonin, and oxidative stress in CKD animals, probably in favor of female sex steroids. These findings emphasize on the importance of gender differences in CKD progression; therefore, considerable attention must be paid to gender in the treatment of CKD. DOI: 10.52547/ijkd.6242